Relationship between Assets and Organizational Structure in the Oil Industry: Regional Aspects - Kryukov, Valery Anatolyevich; Tokarev, Anatoly Nikolaevich (Economy of Regions, 2018)
The article analyzes the relationship between the assets of the oil industry and the industry organizational structure at the level of the producing regions. When considering assets in oil production, we focus on the quantitative and qualitative characteristics of the resource base, primarily on the volumes of recoverable reserves and their depletion. The analysis of the organizational structure of the industry is based on the estimates of the concentration levels of companies in oil production. The performed analysis allows to conclude that in most of the Russian Federation subjects, the organizational structure of the oil industry does not correspond to the assets. For example, in a number of regions, there is a high concentration of companies with a high depletion of reserves. This situation is largely determined by a weak development of small and medium-sized oil business. The development of the organizational structure should be connected with the reform of the institutional conditions in resource management. Currently, these conditions are formed at the federal level and are outside the scope of the regional authorities. Resource base, primarily in mature oil and gas regions, requires stimulating the development of small and mediumsized oil business including support from the regional authorities. The study of regional aspects of the organizational structure of oil production allows identifying the characteristics of certain regions, dependencies and drivers that are not visible when considering these issues at the country level. The obtained results can be used for the development of the system of state regulation in the oil and gas sector both at the federal and regional levels.